2017
DOI: 10.1177/0284185117694511
|View full text |Cite
|
Sign up to set email alerts
|

Virtual monochromatic spectral imaging for the evaluation of vertebral inconspicuous osteoblastic metastases from lung

Abstract: Background The diagnosis of inconspicuous osteoblastic metastases (OBMs) is a challenge in computed tomography (CT) images. The virtual monochromatic spectral (VMS) image of spectral CT is useful for the detection of the low-contrast lesions. Purpose To select the optimal monochromatic level for VMS images of spectral CT for detecting and diagnosing inconspicuous OBMs of the vertebra from lung cancer. Material and Methods Thirty-five patients underwent spectral CT for chest or abdomen. The CT number and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…They suggested that VMI at 70 keV could be the best for diagnosing inconspicuous vertebral metastases, which have a similar density and are therefore not distinguishable from normal vertebrae (Fig. 3) (14).…”
Section: Contrast Enhancementmentioning
confidence: 99%
“…They suggested that VMI at 70 keV could be the best for diagnosing inconspicuous vertebral metastases, which have a similar density and are therefore not distinguishable from normal vertebrae (Fig. 3) (14).…”
Section: Contrast Enhancementmentioning
confidence: 99%
“…Yue et al used postprocessing, and specifically VMI, to improve the detection of subtle osteoblastic metastases of the vertebra from lung neoplasm. The authors demonstrated that VMI 70 keV could be the best tool for diagnosing not clearly evident vertebral metastases, which may have a density very similar to neighboring bone tissue [108]. A recent review [109] showed that VNC images have been used for detecting bone marrow oedema in vertebral fractures, and could increase lesion attenuation.…”
Section: Bonementioning
confidence: 99%